LEGAL REVIEW OF CONTRACTOR'S BREACH OF PERFORMANCE IN COOPERATION RELATIONSHIP WITH SUB CONTRACTORS IN THE WORK ON THE BELAWAN TYPE C HOSPITAL PROJECT - Syawallisa , Syawallisa; Dahlan, Dahlan; Tamaulina Br. Sembring (International Journal of Synergy in Law, Criminal, and Justice, 2025)
In the context of increasingly complex and dynamic infrastructure development, government construction projects have a very important role in driving economic growth and social development in Indonesia. These projects often involve many parties, including main contractors and subcontractors, who collaborate to complete the work according to the specifications and standards set. The cooperative relationship between contractors and subcontractors is very important to ensure the smooth running and success of the project, and to ensure that all parties fulfill their obligations stipulated in the contract. However, in its implementation, problems often occur that can disrupt this relationship, one of which is default. This study aims to determine the legal regulations governing the cooperative relationship between contractors and subcontractors in the implementation of government construction projects, and to determine how legal protection is provided to subcontractors in the event of default by the contractor. The research method used in this study is the normative legal research method, by observing, studying, and understanding legal material, based on the study of positive law. From this study, it can be concluded that the legal rules governing the working relationship between contractors and subcontractors in carrying out government construction projects are regulated in Article 1320 of the Civil Code concerning the requirements for the validity of an agreement and Article 1234 of the Civil Code concerning the elements of default. Article 52 of Law Number 2 of 2017 concerning Construction Services states that service providers and subservice providers in the implementation of construction must operate in accordance with the agreement stipulated in the contract. Article 53 paragraph (3) states that if the service provider transfers part of the work to a subcontractor, the payment request must be accompanied by proof of payment to the subcontractor. The legal protection provided to subcontractors in the event of default by the main contractor includes several aspects, such as the existence of clear contract provisions, which explain the rights and obligations of the parties. Subcontractors have the right to claim compensation through a lawsuit in court as stated in the Medan District Court Decision No. 29/Pdt.G/2022/PN Mdn which resolved the dispute between the plaintiff, Bayu Afandi Nasution, ST, as a subcontractor, with the main defendant, PT Gunakarya Nusantara, who was suspected of default. The decision gave the plaintiff the right to seize collateral against the defendant's account and restore the subcontractor's financial rights as an effort to legally protect the subcontractor's rights.